Effect Of Educative Puzzle Games On The Level Of Creative Thinking In Children Preschool Age 5 - 6 Years At Nidzamiyah Kindergarten - Nurhidayah Nurhidayah; H. Achmad Parjiko Adi Sanjaya; M Choirudin (Universitas Pahlawan Tuanku Tambusai, 2020)
Puzzle educative game is a game for training creativity, regularity, and power of concentration by arranging pieces or parts from particular image. Some previous research showed that using puzzle had an impact on cognitive development,which can stimulate children’s creative thinking abilities so it can increased their creativity. This study was conducted to know the impact of playing puzzle educative game for creative thinking level in preschool 5-6 years old of this study was using one group pre post test design. Subject of the study selected 26 respondents, were taken a samples by total sampling technique. Data collection method used was Torrance Test of Creative Thinking observation sheet. Data analysis of this study using the Wilcoxon Signed Ranks, the result showed was obtained (p = 0.000 < 0.05). This result indicate the significant correlation of puzzle educative games on children creative thinking level. Meanwhile, the difference between posttest results obtained in the study were 29 respondents (73%) had creative thinking good behavior analyzed using Wilcoxon Signed Ranks test obtained a significance level of (p = 0.000 <0.05). Conclusion, there was a difference in outcome for intervention and it shows correlation of puzzle educative games and children creative thinking level. It is expected that nursing institutions can educate teachers for planning activities of learning in schools by using puzzle educative games to maximize the development of children's ability in creative thinking.